2020
DOI: 10.1155/2020/9010496
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Inhibition of Ezrin-Radixin-Moesin Phosphorylation is a Novel Therapeutic Strategy in Rhabdomyosarcoma

Abstract: Intermediate and high-risk rhabdomyosarcoma (RMS) patients have poor prognosis with available treatment options, highlighting a clear unmet need for identification of novel therapeutic strategies. Ezrin-radixin-moesin (ERM) family members are membrane-cytoskeleton linker proteins with well-defined roles in tumor metastasis, growth, and survival. ERM protein activity is regulated by dynamic changes in the phosphorylation at a conserved threonine residue in their C-terminal actin-binding domain. Interestingly, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…Interestingly, total ezrin levels were also reduced after treatment with the inhibitor, which was unexpected. In looking at the literature, most other studies with short duration treatment (1-6 h; Bulut et al, 2012;Proudfit et al, 2020) have not observed a reduction in total ezrin levels, although one study did observe results consistent with ours (Ghaffari et al, 2019). These results may suggest that in certain tissues or with longer time points, as used in this study, negative feedback may act to reduce ezrin protein levels in addition to phosphorylation.…”
Section: Discussionsupporting
confidence: 52%
“…Interestingly, total ezrin levels were also reduced after treatment with the inhibitor, which was unexpected. In looking at the literature, most other studies with short duration treatment (1-6 h; Bulut et al, 2012;Proudfit et al, 2020) have not observed a reduction in total ezrin levels, although one study did observe results consistent with ours (Ghaffari et al, 2019). These results may suggest that in certain tissues or with longer time points, as used in this study, negative feedback may act to reduce ezrin protein levels in addition to phosphorylation.…”
Section: Discussionsupporting
confidence: 52%
“…Both moesin and radixin were found to be expressed in the HTR8 and Swan71 trophoblast cells (Figure 3A-D) but with some cell-specific differences, as a double band could be visible for moesin in the Swan71 trophoblast cell extracts. Moesin has been shown to be post-translationally modified and the presence of different bands has been shown in the context of ERM proteins in numerous cells lines and tissues [39][40][41][42], and it is unclear whether these bands are the result of post-translational modifications or the cross-reactivity of the antibodies. Treatment with either siRNA7 or 9 did not lead to any significant changes in the levels of radixin or moesin (p > 0.05 for all conditions) in our experiments, further demonstrating the specificity of both the knock-downs and our ability to detect ezrin levels in relation to other known ERM factors.…”
Section: Regulating the Expression And Activity Levels Of Ezrin In Ev...mentioning
confidence: 99%
“…NSC305787 and NSC668394 are two inhibitors of ezrin that inhibit ezrin (Thr567) phosphorylation caused by PKCΙ primarily via their binding to ezrin ( Qureshi-Baig et al, 2020 ). Studies are currently being conducted to investigate the antitumor effects of these two compounds, particularly on osteosarcoma ( Shoaib et al, 2022 ), rhabdomyosarcoma ( Proudfit et al, 2020 ), pancreatic cancer ( Lipreri da Silva et al, 2022 ), and colon cancer ( Qureshi-Baig et al, 2020 ). In vitro , cell culture and interference also confirmed that NSC305787 reduced the cellular and malignant molecular behavior of CLL cell lines ( Lipreri da Silva et al, 2021 ).…”
Section: The Pharmacological Inhibition Of Ezrinmentioning
confidence: 99%